De la page blanche à la sculpture, les multiples formes de l’objet-livre - Entretien - Alexandre Melay; Valérie Morisson (Interfaces)
This article is part of a research-creation project where the concept of “format” can be questioned through the medium of the artist’s book. Endowed with specific material and formal qualities, the book-object is an open artistic medium generating hybrid formats; a three-dimensional - sculptural - object with multiple shapes: “systems” of formats such as the “accordion-book”, the “building-book” or even the “sound-book”. These formal inventions create new phenomenological experiences as our physical presence is called upon in a movement including the gaze and the body. The book-object with its singular shapes and its unconventional “formats”, becomes a sculpture, a piece of architecture, an exhibition space constructing a new spatiality and mobilising various senses.